Recent Advances in Sortase-Catalyzed Ligation Methodology - Antos, John M. (Curr Opin Struct Biol, 2016)
The transpeptidation reaction catalyzed by bacterial sortases continues to see increasing use in the construction of novel protein derivatives. In addition to growth in the number of applications that rely on sortase, this field has also seen methodology improvements that enhance reaction performance and scope. In this opinion, we present an overview of key developments in the practice and implementation of sortase-based strategies, including applications relevant to structural biology. Topics include the use of engineered sortases to increase reaction rates, the use of redesigned acyl donors and acceptors to mitigate reaction reversibility, and strategies for expanding the range of substrates that are compatible with a sortase-based approach.